Assessing the ecosystem services of urban argiculture in Klang Valley - Zamrillah, Mohamad Hafiz Syazwan (2018)
Natural ecosystems are an important contributor to the sustainability of a country, especially Malaysia. Among the benefits available from natural ecosystems are food needs, transportation of energy sources and medicines. As urbanization progresses in many areas of Malaysia, it has raised issues such as food safety, pollution of nature, as well as devaluation of landscapes in urban areas. Urban agricultural practices are a concern in Malaysia because of the potential for food safety, the sustainability of urban areas. Benefits available through urban agricultural practices are the reason for community assessment of ecosystem services based on urban agricultural practices. Cross-section data was collected through structured questionnaires, to obtain information on community awareness of the environmental quality of the city, as well as their perceptions of urban agricultural practices. Descriptive analysis is used to know about the socio-demographic profile of respondents. Factor analysis is used to identify the link between the level of community awareness of the environmental quality of the city and their perceptions of the ecosystem services nature with their socio-demographic profile.